Forecasting linear aliphatic copolyester degradation through modular block design. (August 2016) - Arias, Veluska; Olsén, Peter; Odelius, Karin; Höglund, Anders; Albertsson, Ann-Christine
Abstract: The development of efficient methods to predict the degradation of renewable polymeric materials is continuously sought in the field of polymer science. Herein, we present a modular build-up approach to create polyester-based materials with forecasted degradation rates based on the hydrolysis of the constituent polymer blocks. This involved the strategic combination of critical factors affecting polyester hydrolysis, i.e . hydrophobicity and degree of crystallinity. The starting point of this method was a toolbox of polymers with different hydrophobicities and degrees of crystallinity, as well as an understanding of their inherent differences in hydrolysis rate. Knowledge of the hydrolysis of each polymer block module enabled the prediction of the overall degradation behavior of the constructed copolymers. Taking advantage of the primary factors that affect polymer degradation, block copolymers could be independently designed to incorporate soft or rigid and faster or slower degradation properties. This approach generated a shift for how molecular design can be used to predict the degradation behavior of intended materials for different applications. Graphical abstract: